If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + 8 + -12x + 6 = 18x + 9 Reorder the terms: 8 + 6 + 16x + -12x = 18x + 9 Combine like terms: 8 + 6 = 14 14 + 16x + -12x = 18x + 9 Combine like terms: 16x + -12x = 4x 14 + 4x = 18x + 9 Reorder the terms: 14 + 4x = 9 + 18x Solving 14 + 4x = 9 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 14 + 4x + -18x = 9 + 18x + -18x Combine like terms: 4x + -18x = -14x 14 + -14x = 9 + 18x + -18x Combine like terms: 18x + -18x = 0 14 + -14x = 9 + 0 14 + -14x = 9 Add '-14' to each side of the equation. 14 + -14 + -14x = 9 + -14 Combine like terms: 14 + -14 = 0 0 + -14x = 9 + -14 -14x = 9 + -14 Combine like terms: 9 + -14 = -5 -14x = -5 Divide each side by '-14'. x = 0.3571428571 Simplifying x = 0.3571428571
| 7n=2n-20 | | y^2=x^3+9x+17 | | a+(5+3a)=2a-7 | | 4(2x+3)=2(5x-2)+6 | | 9-6y=24-8y+7 | | 3t^2=6t-12 | | 4y-7+2y=5y-6+9 | | 13-2x= | | x-5y=3v | | 2x+5=3x+10 | | 3a-4=A | | 2x-20=5x-5 | | 189-5x=31x+17 | | -35-4x=13-10x | | 51-3x=7x+21 | | 6x+14=91-5x | | 6x+36=14x-52 | | (6x-5)(6x-5)=36x-25 | | 2a+2b+2c=262 | | 2n-20=7n | | 6x^2-10x+1=0 | | 19-3=x-8 | | 54x+15=16 | | 4=3x-10+x-2 | | 15-6(2x-5)=50 | | -7x-12=-3x-16 | | 3x+3=5x-11 | | x+12=5x-16 | | 24-5y=3(10-y) | | -x^4+13x^2-3=0 | | x^3-2x^2-5x+6=0 | | x+5x=63 |